Energy Audit on Solar Energy Switching - Sheela, T.; R, Manju; S, Harini (2021 4th International Conference on Computing and Communications Technologies (ICCCT), 2021)
Disruption in power supply in cities appears to have become the norm nowadays. TNEB has installed around 10,000MW of power producers still, we have power outages as the requirement have drastically increased. So, to prevent further outages, we have incorporated renewable sources of energy as a backup. we have built a system that efficiently switches from usual electricity to solar source energy seamlessly. Research on the electricity consumed there days states that the total usability is being increased by 4% all over India during the pandemic, which had led to a situation where the power cuts are prone. We would like a propose an idea where a solar inverter with a minimum budget is used and all the current stored in the batteries is being efficiently used by the household on daily basis. Our Audit system states the best way and the amount of energy you can save along with money on a monthly basis. This project can be very impactful as solar energy is a renewable source of energy and is available abundantly, which also makes the process eco-friendly. The Energy Audit System gives you the best amount you can save with respect to your household. an auto-switching circuit is being designed for the day-to-day purpose using a relay.